What keeps a body moving? The brain-derived neurotrophic factor val66met polymorphism and intrinsic motivation to exercise in humans - Caldwell Hooper, A.; Bryan, A.; Hagger, Martin (Springer New York LLC, 2014)
Individuals who are intrinsically motivated to exercise are more likely to do so consistently. In previous research, those with at least one copy of the methionine (met) allele in the brain-derived neurotrophic factor gene (BDNF; rs6265) had greater increases in positive mood and lower perceived exertion during exercise. This study examined whether genotype for BDNF is also related to intrinsic motivation, measured by self-report during a treadmill exercise session and a free-choice behavioral measure (continuing to exercise given the option to stop) among 89 regular exercisers (age M = 23.58, SD = 3.95). Those with at least one copy of the met allele reported greater increases in intrinsic motivation during exercise and were more likely to continue exercising when given the option to stop (55 vs. 33 %). Results suggest that underlying genetic factors may partially influence perceptions of inherent rewards associated with exercise and might inform the development of individually targeted interventions.